SURGICAL TREATMENT OF COMPLICATED DUCTUS CHOLEDOCHUS HYDATIDOSIS DURING THE COVID-19 PANDEMIC: EFFECTIVENESS AND LIMITATIONS OF RADIOLOGICAL SERVICES AND SURGERY IN EXTRAORDINARY CONDITIONS - Doklestić, Krstina S; Vasin, Dragan; Micić, Dušan; Grubor, Nikola; Resanovic, Vladimir; Lešević, Ivana; Duka, Ognjen; Bajić, Vinka; Vuković, Goran; MIjović, Ksenija; Pavlović, Aleksandar; Mitrović, Jelena; et al. (Sanamed, 2024)
Introduction: While uncomplicated echinococcal cysts can grow in the liver for years without symptoms, complicated hydatid cysts (CHC) present distinct clinical characteristics that necessitate urgent treatment. Case Report: We present a case of acute biliary obstruction, cholangitis, and sepsis due to massive choledocho-hydatididosis in an 84-year-old COVID-positive patient during the COVID-19 pandemic. Imaging revealed a multicystic lesion in liver segments V and VIII that compressed surrounding liver tissue, leading to intrahepatic duct dilation. A daughter cyst in the ductus choledochus was confirmed during surgery. An attempt at endoscopic retrograde cholangiopancreatography (ERCP) was unsuccessful. We performed an open pericystectomy with total cystectomy and choledochotomy, carefully evacuating all hydatid cysts. The postoperative course was uneventful, and the patient was discharged without surgical complications. Conclusion: Complicated hydatid cysts (CHC) leading to acute biliary obstruction require prompt diagnosis and indicate the need for rapid evacuation of the cyst and correction of complications.